2002
DOI: 10.1046/j.1537-2995.2002.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing the frequency of acute reactions to plasma‐removed platelets and prestorage WBC‐reduced platelets

Abstract: The frequency of reactions to plasma-removed platelets and prestorage WBC-reduced platelets was not significantly different; however, the power of the study for this comparison was low. There was no difference in the frequency of reactions to the two types of prestorage WBC-reduced platelets. The frequency of severe reactions to prestorage WBC-reduced platelets is low, occurring in only 1 to 2 percent of transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
176
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(189 citation statements)
references
References 35 publications
5
176
0
8
Order By: Relevance
“…35 In the current investigation it was not possible to study another important potential benefit of prestorage leukoreduction (ie, a reduction in FNHTRs) since the method of recording these events at our center changed over the study period. [36][37][38][39][40] Similarly, the other predicted advantages of prestorage leukoreduction, such as a reduction in transfusion-associated infections and posttransfusion immune suppression, require further study. [41][42][43][44] If these benefits are confirmed they will add support to the results of this study and the growing body of literature in favor of prestorage leukoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…35 In the current investigation it was not possible to study another important potential benefit of prestorage leukoreduction (ie, a reduction in FNHTRs) since the method of recording these events at our center changed over the study period. [36][37][38][39][40] Similarly, the other predicted advantages of prestorage leukoreduction, such as a reduction in transfusion-associated infections and posttransfusion immune suppression, require further study. [41][42][43][44] If these benefits are confirmed they will add support to the results of this study and the growing body of literature in favor of prestorage leukoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between bleeding and thrombocytopenia has been well described, and bleeding is a frequent complication occurring in this patient population. [1][2][3][4][5][6][7][8] Despite the administration of prophylactic or therapeutic platelet (PLT) transfusions, these patients are still at risk of bleeding.…”
mentioning
confidence: 99%
“…It has been reported that cytokine levels are more in PC stored at 22°C than in red cells stored at 4°C because higher temperature may allow greater metabolic activity of cytokine producing WBCs. Heddle et al [16] demonstrated this by separating cellular and plasma or supernatant portion of PCs. It was shown that most reactions to platelets were caused by WBC derived cytokines that accumulate in the plasma portion of the component.…”
Section: Discussionmentioning
confidence: 97%
“…According to them the release of cytokines from dead WBCs is also possible as they showed that IL-8 mRNA levels increased from Day 1 to Day 8 using semi quantitative RT-PCR. Heddle et al [16] demonstrated that if WBC counts are reduced to a concentration lower than 5 9 10 6 /unit the cytokine release is reduced . Different studies have adopted different techniques for leukoreduction.…”
Section: Discussionmentioning
confidence: 99%